In Vitro Efficacy of Curcumin-Loaded Amine-Functionalized Mesoporous Silica Nanoparticles against MCF-7 Breast Cancer Cells - Zahra Mohebian; Mirzaagha Babazadeh; Nosratollah Zarghami (Tabriz University of Medical Sciences, 2023)
Purpose: Mesoporous silica nanoparticles (MSNs) have drawn substantial interest as drug nanocarriers for breast cancer therapy. Nevertheless, because of the hydrophilic surfaces, the loading of well-known hydrophobic polyphenol anticancer agent curcumin (Curc) into MSNs is usually very low. Methods: For this purpose, Curc molecules were loaded into amine-functionalized MSNs (MSNs-NH2 -Curc) and characterized using thermal gravimetric analysis (TGA), Fourier-transform infrared (FTIR), field emission scanning electron microscope (FE-SEM), transmission electron microscope (TEM), Brunauer-Emmett-Teller (BET). MTT assay and confocal microscopy, respectively, were used to determine the cytotoxicity and cellular uptake of the MSNs-NH2 - Curc in the MCF-7 breast cancer cells. Besides, the expression levels of apoptotic genes were evaluated via quantitative polymerase chain reaction (qPCR) and western blot. Results: It was revealed that MSNs-NH2 possessed high values of drug loading efficiency and exhibited slow and sustained drug release compared to bare MSNs. According to the MTT findings, while the MSNs-NH2 -Curc were nontoxic to the human non-tumorigenic MCF-10A cells at low concentrations, it could considerably decrease the viability of MCF-7 breast cancer cells compared to the free Curc in all concentrations after 24, 48 and 72 hours exposure times. A cellular uptake study using confocal fluorescence microscopy confirmed the higher cytotoxicity of MSNs-NH2 -Curc in MCF-7 cells. Further, it was found that the MSNs-NH2 -Curc could drastically affect the mRNA and protein levels of Bax, Bcl-2, caspase 3, caspase 9, and hTERT relative to the free Curc treatment. Conclusion: Taken together, these preliminary results suggest the amine-functionalized MSNs-based drug delivery platform as a promising alternative approach for Curc loading and safe breast cancer treatment.